Mesenteric desmoid tumor after bariatric surgery: a case report - Navarini, Daniel; Albuquerque, Antônio Benincá; Rovani, André Luca Boeira; da Silva, Victor Vasconcelos; Ranzolin, Bernardo Antoniolli; Reffatti, Diego; Perin, Ramir Luan; Madalosso, Carlos Augusto Scussel (Clinical and Biomedical Research, 2020)
We report the case of a 37-year-old woman investigated for left flank pain, 1 year after bariatric surgery (Roux-en-Y gastric bypass). Abdominal computed tomography (CT) revealed a solid, heterogeneous and expansive intra-abdominal lesion, measuring 9.3x9.4x10.4cm, compressing adjacent structures with no signs of invasion. The main diagnostic hypothesis considered was desmoid tumor/Schwannoma and a ileocolectomy with partial mesenteric resection was performed. A histopathological and immunohistochemical analysis confirmed the diagnosis of mesenteric desmoid tumor.